Sustentabilidade em gerenciamento de projetos de conjuntos sinfônicos: perspectivas para a música de concerto no século XXI - Salles, Felipe Aragão Campos (2022)
The forms of sustainable thinking have been gaining prominence in several sectors, and their models (GRI, Ethos, Dow Jones, among others) being remodeled at specific levels. The gap, in the musical category, is the ways in which sustainability (in its economic, social and environmental tripod) is constructed in the context of concert music in the 21st century. We start from the question-problem: How to integrate the traditional tools of sustainability together with the practices of concert music, in order to propose a set of practices that optimize sustainability in the management of communication of musical projects? The general objective is to propose a theoretical and empirical model of sustainability in the concert music project management, adhering to the Sustainable Development Goals of the 2030 Agenda. To confirm this objective, the research adopts a qualitative method, combining: 1) Content analysis: to bring together the main business sustainability models and initiatives perceived in concert music in the economic, social and environmental dimensions and 2) Semi- structured interviews: in which experts in concert music project management were interviewed to bring new possibilities. The results point to a set of practices adherent to the 21st century scenario, with an extensive use of digital media (Osesp, Berlin Philharmonic), an audience formation and democratic mechanisms of music education (El Sistema).(AU)